Toxoplasma gondii Tetravalent Chimeric Proteins as Novel Antigens for Detection of Specific Immunoglobulin G in Sera of Small Ruminants - Holec-Gąsior, Lucyna (Animals (Basel), 2019)
SIMPLE SUMMARY: Toxoplasma gondii infection leads to large economic losses in the sheep and goat industry worldwide and is considered to be one of the main causes of infectious ovine and caprine abortion. Moreover, in countries where sheep and goat meat are frequently consumed, T. gondii infection in small ruminants may also pose a public health risk. Due to its medical and veterinary importance, it is essential to study the seroprevalence of T. gondii infection among farm animals and humans. This requires the development of new, low-cost diagnostic methods such as enzyme immunoassays based on recombination antigens. Thus, the study aimed to evaluate the reactivity of four different tetravalent chimeric proteins containing immunodominant regions from the AMA1 (apical membrane antigen 1), SAG2 (surface antigen 2), GRA1 (dense granule antigen 1), GRA2 (dense granule antigen 2), and ROP1 (rhoptry antigen 1) T. gondii antigens with specific IgG from the sera of small ruminants. The results demonstrate that an IgG ELISA (enzyme-linked immunosorbent assay) based on one of these chimeric proteins (AMA1-SAG2-GRA1-ROP1) may be a useful test for the determination of T. gondii infection in small ruminants. ABSTRACT: The detection of Toxoplasma gondii infection in small ruminants has important significance for public health and veterinary medicine. This study, for the first time, describes the reactivity of four tetravalent chimeric proteins (AMA1(N)-SAG2-GRA1-ROP1, AMA1(C)-SAG2-GRA1-ROP1, AMA1-SAG2-GRA1-ROP1, and SAG2-GRA1-ROP1-GRA2) containing immunodominant regions from the AMA1 (apical membrane antigen 1), SAG2 (surface antigen 2), GRA1 (dense granule antigen 1), GRA2 (dense granule antigen 2), and ROP1 (rhoptry antigen 1) with specific IgG antibodies from the sera of small ruminants with the use of an indirect enzyme-linked immunosorbent assay (ELISA). The reactivity of individual chimeric antigens was analyzed in relation to the results obtained in IgG ELISA based on a Toxoplasma lysate antigen (TLA). All chimeric proteins were characterized by high specificity (between 96.39% to 100%), whereas the sensitivity of the IgG ELISAs was variable (between 78.49% and 96.77%). The highest sensitivity was observed in the IgG ELISA test based on the AMA1-SAG2-GRA1-ROP1. These data demonstrate that this chimeric protein can be a promising serodiagnostic tool for T. gondii infection in small ruminants.